Pembangunan Aplikasi Asesmen Kompetensi Untuk Meningkatkan Kinerja LSP - Sabella, Billy; Fathurrahmani, Fathurrahmani; Aprianti, Winda; Achmad, Ferdiyansyah; Tina, Ridha Rahma (Journal of Information System Research (JOSH), 2024)
Professional Certification Institute (PCI) of Politeknik Negeri Tanah Laut has the task of carrying out competency assessments for prospective graduates. Competency assessment management starting from registration, the certification process, and reporting certification results is still done manually, so it requires a long management time and is prone to errors. Ineffective management of the 2 existing schemes will further impact the decline in the performance of the PCI of Politeknik Negeri Tanah Laut which is currently in the process of increasing the scope of 16 schemes. This is the rationale for the need for an application that can help manage competency certification data so as to improve Professional Certification Institute performance. The method used in this research starts from the stages of needs identification, design, implementation, testing and evaluation, implementation and training, and system development. The research that has been carried out provides the results of the PCI of Politeknik Negeri Tanah Laut information system which was built and has features for managing assessment data, assessor data, certification scheduling, competency test material components, certification reporting and activity documentation. The system built has been tested using black box testing and shows 100% successful feature functionality. System evaluation using User Acceptance Testing on 12 respondents showed acceptance results of 91.50%. Based on the test results, the assessment application that has been built helps improve Professional Certification Institute performance.